Mesoamerican nephropathy: a narrative review - Oza, Yugam R.; Mannava, Anjali S.; Tousif, Meirajuddin J.; Shah, Jash K.; Gondalia, Shrinath V.; Mevawala, Hardik B.; Joshi, Helly M.; Gor, Nancy M.; Jivarani, Nishi J.; Dharani, Dhruv U. (International Journal of Research in Medical Sciences, 2023)
Mesoamerican nephropathy (MeN) also known as chronic kidney disease of unknown etiology (CKDu) is prevalent in agriculturally rich areas. The most widely accepted pathophysiological explanation for MeN is chronic dehydration caused by prolonged exposure to the sun. Other theories include oxidative stress, chronic inflammation, infection and tubulointerstitial fibrosis. The clinical presentation is quite vague and is diagnosed similar to CKD from any cause using blood, urine analysis and ultrasound. The study highlights the need for interdisciplinary cooperation among physicians, epidemiologists, toxicologists, and geneticists while identifying significant research gaps and future objectives. Occupational health related to agriculture is not emphasised enough especially in third world countries where a large chunk of population heavily depend on farming. To safeguard the population at risk, the significance of community-based initiatives, occupational health measures, and regulatory changes is emphasised.